Correction: Aksic et al. The Neuroprotective Effect of Neural Cell Adhesion Molecule L1 in the Hippocampus of Aged Alzheimer’s Disease Model Mice. Biomedicines 2024, 12, 1726 - Miljana Aksic; Igor Jakovcevski; Mohammad I. K. Hamad; Vladimir Jakovljevic; Sanja Stankovic; Maja Vulovic (Biomedicines)
There was an error in the original publication [...]